Verlegenheitslösung oder unternehmerische Chance? Das Bundesministerium für Wirtschaft und der Einstieg von Röchling als Mehrheitsaktionär bei Rheinmetall (1953–1956) - Herbert Elzer (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– In the early 1950s state property of large industrial plants was regarded as a burden by the West German Government. Rheinmetall-Borsig, well-known as a former armaments company, was devastated and in sore need of an ingenious entrepreneur with financial capabilities. The Federal Ministries of Economy and Finance appraised the Saarland-based Roechling'sche Eisen- und Stahlwerke as suitable for this purpose. It had been ousted from French-dominated Saarland und had established commercial relations with the renowned Swiss armaments company Hispano-Suiza. Why both facts did not hamper Roechling's ambitions and even boosted its chances to become majority shareholder of Rheinmetall is described in this paper, which also sheds some light on the problems of state-owned enterprises after World War II.
Keywords: N44; N84; 330; Rheinmetall-Borsig; Roechling; armaments; Saarland problem; status of Berlin; re-privatization; state-owned enterprises